2022
DOI: 10.1021/acsomega.1c06220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Myristate on the Induced Circular Dichroism Spectra of Aripiprazole Bound to Human Serum Albumin: A Structural–Chemical Investigation

Abstract: The effects of myristate on the induced circular dichroism spectra of aripiprazole (ARP) bound to human serum albumin (HSA) were investigated. High concentrations of myristate reversed the Cotton effects induced in the ARP–HSA system. The observed ellipticities increased with increasing drug concentration up to an ARP-to-HSA molar ratio of 1:1 and then decreased, indicating that the extrinsic Cotton effects were generated by the binding of ARP molecules to the high- and low-affinity sites in HSA. The data for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…As a result, the local chamber corresponding to the thiomethylene linker storage becomes narrow, which is suitable for the thiomethylene linker, but it cannot accommodate moieties that are bulkier than the thiomethylene linker due to steric hindrance. The side chain of Tyr161 usually stacks with that of Tyr138 as shown in the substrate-free structure within subdomain IB of HSA, and its orientation is close to that of the cefazolin complex. In the HSA complex structure with ceftriaxone, the R1 side chain of ceftriaxone coincides with the position of the side chain of Tyr161 in the substrate-free structure, resulting in the induction of rotation of Tyr161 to avoid steric clash.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As a result, the local chamber corresponding to the thiomethylene linker storage becomes narrow, which is suitable for the thiomethylene linker, but it cannot accommodate moieties that are bulkier than the thiomethylene linker due to steric hindrance. The side chain of Tyr161 usually stacks with that of Tyr138 as shown in the substrate-free structure within subdomain IB of HSA, and its orientation is close to that of the cefazolin complex. In the HSA complex structure with ceftriaxone, the R1 side chain of ceftriaxone coincides with the position of the side chain of Tyr161 in the substrate-free structure, resulting in the induction of rotation of Tyr161 to avoid steric clash.…”
Section: Discussionmentioning
confidence: 93%
“…In clinical conditions, the drugs bound to subdomain IB as a secondary binding site would not be a major concern if their plasma concentrations are sufficiently below that of HSA. However, we reported that some drugs show translocations to their secondary binding sites due to competition for the primary binding site with the co-administrated drugs or endogenous compounds. , While these drugs should be paid attention to, it is challenging to predict such translocation events since they occur under specific underlying conditions or in combination with specific co-administrated drugs. Moreover, while our present study suggests that subdomain IB of HSA is the primary binding site on HSA for the cephalosporins showing higher plasma protein binding, some cephalosporins, especially those showing lower plasma protein binding, may possess other binding sites on HSA.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of NSAIDs in the albumin/drugs molar ratio of 1:8 results in spectra that are similar in shape and peak position compared with the spectrum of non-bound HSA. The secondary structure contents (%) of non-bound albumin and HSA:NSAIDs are depicted in Figure 5B and summarized in Table 3, showing a slight decrease in the α-helix content (7.1% and 7.6% in the presence of KTF and KTL, respectively), resulting in slight increases in the antiparallel β-sheet, turns, and other structural contents [63]. It was reported that non-bound albumin comprises around 67% α-helices, 10% turns, and 23% random coils [64].…”
Section: Conformational Perturbation Of Hsa Upon Nsaid Bindingmentioning
confidence: 99%
“…Figure10. Comparisons of the binding position of MP (yellow stick) with those of warfarin (A, orange stick, PDB: 2BXD30 ), CMPF (B, magenta stick, PDB: 2BXA30 ), myristate (C, gray stick, PDB: 7VR931 ), and indomethacin (D, green stick, PDB: 2BXM30 ) at subdomain IIA.…”
mentioning
confidence: 99%